COMPARISON OF ELECTRONIC COMMERCE REGULATIONS IN INDONESIA AND THAILAND - Putri, Nur Alvia; Lubis, Mhd Teguh Syuhada (Pena Cendekia Insani, 2026)
The development of electronic commerce (e-commerce) has brought significant changes to the national and regional trade systems in the ASEAN region. Indonesia and Thailand, as countries with rapid digital economic growth, have each established their own e-commerce regulatory frameworks, but with different legal approaches. This research aims to analyze and compare the regulation of electronic commerce in Indonesia and Thailand, particularly in the aspects of consumer protection and legal certainty of digital transactions. This study employs a normative legal research method with a legislative and comparative approach. The research results show that Indonesia emphasizes consumer protection thru the Consumer Protection Law, the Electronic Information and Transactions Law, and Government Regulation Number 80 of 2019 concerning Electronic System Trade, while Thailand places more emphasis on the legal recognition of electronic transactions and digital system security thru the Electronic Transactions Act B.E. 2544 (2001), the Consumer Protection Act (No. 4) B.E. 2562 (2019), and the Computer Crime Act B.E. 2550 (2007).